SISTEM PAKAR DIAGNOSA GANGGUAN KEHAMILAN BERBASIS WEB DENGAN MENGGUNAKAN METODE FORWARD CHAINING PADA RSIA RP SOEROSO - Frieyadie, Frieyadie; Aryanti, Herlina (LPPM Universitas Nusa Mandiri, 2013)
The risk of maternal mortality is also higher due to the delay factor is too late to recognize the danger, delay making a decision to be referred, too late to health facilities during emergencies, and too late to obtain adequate services by health workers. One of the high maternal mortality rates in Indonesia is due to the relatively low coverage of aid by health professionals. obstetric health services are very limited so it has not been able to cope with high-risk pregnant women and the lack of information about the symptoms that arise during pregnancy and the dangers of high-risk pregnancies. The method used in this paper, the method of Forward Chaining. The purpose of this study to design an expert system for the diagnosis of early pregnancy disorders Mother and Child Hospital (RSIA) RP Soeroso with web-based. Improving the quality of health services RSIA RP Soeroso both from a technical point of health and clear information about pregnancy disorders. Give the action or relief at the time of the symptoms women experience pregnancy disorder. Application experts who built got a good response and can assist in detecting disorders of pregnancy in pregnant women.